An experiment on heat extraction from a deep geothermal well using a downhole coaxial open loop design. (15th October 2019) - Dai, Chuanshan; Li, Jiashu; Shi, Yu; Zeng, Long; Lei, Haiyan
Highlights: A Heat extraction test in a geothermal well was performed with a coaxial open loop. Comparing to the closed loop, the proposed open loop can obtain greater heat output. The outlet temperature can reach stability more quickly. A simple conceptual model was proposed that matches well with the experimental data. Abstract: We report a field heat extraction test from a deep geothermal well using a downhole coaxial open loop design in Tanggu, Tianjin China, which is different from most previous studies in that the well casing is closed to the geothermal reservoir. A downhole pump installed in the inner tube pumped the geothermal fluids to the surface. After releasing heat by flowing through a plate heat exchanger, the geothermal fluid returned to the aquifer completely and naturally by gravity through the annular section between the inner tube and the borehole wall. The proposed design realizes a sustainable and clean way of "no water withdrawn but heat only" in geothermal utilization. The experimental test well was used as a reinjection well for two years, and the maximum measured temperature in the well before the experiment was only 51 °C. The experimental results show that the proposed configuration worked very well in extracting heat from a deep geothermal reservoir. The system's stable heat output can reach approximately 275 kW after two weeks of continuous heat extraction, which was much larger than the theoretically calculated value for deep borehole heat exchangers by using the heat conduction model.